Ex vivo tools for the clonal analysis of zebrafish hematopoiesis - Svoboda, Ondrej; Stachura, David L; Machonova, Olga; Zon, Leonard I; Traver, David; Bartunek, Petr (Nature protocols, 2016)
This protocol describes the ex vivo characterization of zebrafish hematopoietic progenitors. We show how to isolate zebrafish hematopoietic cells for cultivation and differentiation in colony assays in semi-solid media. We also describe procedures for the generation of recombinant zebrafish cytokines and for the isolation of carp serum, which are essential components of the medium required to grow zebrafish hematopoietic cells ex vivo. The outcome of these clonal assays can easily be evaluated using standard microscopy techniques after 3-10 d in culture. In addition, we describe how to isolate individual colonies for further imaging and gene expression profiling. In other vertebrate model organisms, ex vivo assays have been crucial for elucidating the relationships among hematopoietic stem cells (HSCs), progenitor cells and their mature progeny. The present protocol should facilitate such studies on cells derived from zebrafish.
Keywords: Zebrafish; Recombinant Proteins; Hematopoiesis; proteiny dánia pruhovaného; Culture Media; Zebrafish Proteins; kultivační média; cytokiny; buněčné kultury; dánio pruhované; kapři; stanovení celkové genové exprese; hematopoetické kmenové buňky; Gene Expression Profiling; rekombinantní proteiny; Animals; zvířata; hematopoéza; Cell Culture Techniques; Carps; Cytokines; Hematopoietic Stem Cells; Molecular Biology; molekulární biologie